Toward an interactional approach to multilingualism: Ideologies and practices in the northwest Amazon. (September 2021) - Stenzel, Kristine; Williams, Nicholas
Abstract: This study examines language ideologies and communicative practices in the multilingual Vaupés region of northwestern Amazonia. Following a comparative overview of the Vaupés as a 'small-scale' language ecology, it discusses claims from existing ethnographic work on the region in light of data from a corpus of video-recordings of sociolinguistic interviews and spontaneous everyday conversations. It shows how a practice-based and interdisciplinary approach combining language documentation methodology and ethnographic, structural linguistic, and interactional perspectives can contribute to understanding of macro and micro aspects of multilingualism, thus contributing to future work on the Vaupés, typologies of small-scale multilingual ecologies, and language contact research. Highlights: Diverse language ecologies are caught up in ongoing and sometimes overpowering geopolitical forces. Defining small-scale multilingualism requires attention to both ideologies and practices. The Amazonian Vaupés is characterized by overlapping multilingual systems. Multilingualism in the Vaupés is undergoing rapid change due to 'Tukanization'. East Tukano speakers deploy multilingual resources for specific interactional purposes.